2021
DOI: 10.48550/arxiv.2106.08241
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Magnetic-buoyancy-induced mixing in AGB Stars: fluorine nucleosynthesis at different metallicities

D. Vescovi,
S. Cristallo,
S. Palmerini
et al.

Abstract: Asymptotic giant branch (AGB) stars are considered to be among the most significant contributors to the fluorine budget in our Galaxy. While at close-to-solar metallicity observations and theory agree, at lower metallicities stellar models overestimate the fluorine production with respect to heavy elements. We present 19 F nucleosynthesis results for a set of AGB models with different masses and metallicities in which magnetic buoyancy acts as the driving process for the formation of the 13 C neutron source (t… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 56 publications
1
1
0
Order By: Relevance
“…They conclude from their studies, however, that AGB stars are not the main contributors of F in the solar neighborhood (core collapse SNe are) in agreement with chemical evolution models extant in the literature, e.g., Kobayashi et al (2011). Further analysis by this same team presented in Vescovi et al (2021) also finds that F abundance in AGB stars is directly related to the average s-process abundance <s> such that [F/Fe] and [<s>/Fe] increase together (see their Figure 2, upper panel). Overall, they also find that their stellar models better reproduce the F/H abundance observations when magnetic buoyancy "acts as the driving force for the formation of the 13 C neutron source" in metal-poor AGB stars during TDU.…”
Section: Fluorinesupporting
confidence: 68%
“…They conclude from their studies, however, that AGB stars are not the main contributors of F in the solar neighborhood (core collapse SNe are) in agreement with chemical evolution models extant in the literature, e.g., Kobayashi et al (2011). Further analysis by this same team presented in Vescovi et al (2021) also finds that F abundance in AGB stars is directly related to the average s-process abundance <s> such that [F/Fe] and [<s>/Fe] increase together (see their Figure 2, upper panel). Overall, they also find that their stellar models better reproduce the F/H abundance observations when magnetic buoyancy "acts as the driving force for the formation of the 13 C neutron source" in metal-poor AGB stars during TDU.…”
Section: Fluorinesupporting
confidence: 68%
“…We note that the work of Abia et al (2019) and Vescovi et al (2021) have shown recently that the contributions of 19 F from AGB stars are a significantly smaller percentage of the budget than originally predicted by Jorissen et al (1992). Vescovi et al (2020Vescovi et al ( , 2021 incorporate magnetically induced 13 C pockets in their models which result in lower proton abundances. They thus produce less 14 N and 19 F than models with 13 C pockets produced by convective overshoot.…”
Section: Fluorinementioning
confidence: 44%